2014
DOI: 10.1017/s0033291714001159
|View full text |Cite
|
Sign up to set email alerts
|

ZNF804A genetic variation (rs1344706) affects brain grey but not white matter in schizophrenia and healthy subjects

Abstract: Our findings demonstrate effects of ZNF804A genetic variation on brain structure, with diverging regional effects in schizophrenia patients and healthy controls in frontal and temporal brain areas. These effects, however, might be dependent on the impact of other (genetic or non-genetic) disease factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…About the temporal cortex, we found that ZNF804A rs1344706 was associated with the cortical thickness in the left superior temporal in the SZ patients. This result is consistent with several previous studies, which showed that ZNF804A s1344706 was associated with the temporal cortex [Mohnke et al, ; Nenadic et al, ]. Temporal cortex also has been showed to be involved in the neuropathological mechanism of SZ [Sun et al, ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…About the temporal cortex, we found that ZNF804A rs1344706 was associated with the cortical thickness in the left superior temporal in the SZ patients. This result is consistent with several previous studies, which showed that ZNF804A s1344706 was associated with the temporal cortex [Mohnke et al, ; Nenadic et al, ]. Temporal cortex also has been showed to be involved in the neuropathological mechanism of SZ [Sun et al, ].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the risk allele (T) in ZNF804A rs1344706, compared to the non‐risk allele (G), was associated with a smaller cortical surface area in the left superior frontal, and with a lower cortical volume in the left superior frontal in schizophrenia. Previous studies also showed that ZNF804A s1344706 was associated with the prefrontal cortex [Esslinger et al, ; Nenadic et al, ; Schultz et al, ]. Many studies [Glahn et al, ] have demonstrated that the frontal cortex is associated with the neuropathological mechanism of schizophrenia.…”
Section: Discussionmentioning
confidence: 94%
“…In reporting the rs1344706 association with heroin addiction, Sun et al (in press) showed that its risk allele and haplotype were associated with greater gray matter volume across several human brain regions; they detected an interaction with heroin addiction specifically in the left sensorimotor cortex, a region that is relevant for developing and preserving addiction, whereby the risk haplotype was associated with greater gray matter volume in heroin abusers but lower gray matter volume in controls. This association involving rs1344706 and gray matter by disease state is consistent with prior findings in healthy individuals (Voineskos et al ) and schizophrenia cases and controls (Nenadic et al ). These studies further linked rs1344706‐A to reduced cognitive function (Sun et al in press; Voineskos et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several genome-wide association studies (GWAS) suggested that a classical C2H2-type zinc finger domain containing protein ZNF804a is one of the most susceptible genes for schizophrenia and bipolar disease [19,20]. Human ZNF804A has one C2H2 domain at N'-terminal, which is supposed to bind DNA in a sequence-specific manner (Figure 1).…”
Section: Mental Illness With Znfsmentioning
confidence: 99%
“…Human ZNF804A has one C2H2 domain at N'-terminal, which is supposed to bind DNA in a sequence-specific manner (Figure 1). A number of genetic variations, such as single nucleotide polymorphism (SNP) rs1344706 within the ZNF804A gene, are of risky variants for schizophrenia in European populations [20,21]. But a recent study showed inconformity with the results in Han Chinese [22].…”
Section: Mental Illness With Znfsmentioning
confidence: 99%